2019
DOI: 10.1080/13696998.2019.1636382
|View full text |Cite
|
Sign up to set email alerts
|

The real-world economic impact of home-based video electroencephalography: the payer perspective

Abstract: Aims: Electroencephalography (EEG) is an established method to evaluate and manage epilepsy; video EEG (VEEG) has significantly improved its diagnostic value. This study compared healthcare costs and diagnostic-related outcomes associated with outpatient vs inpatient VEEG among patients with epilepsy in the US. Materials and methods: This study used Truven MarketScan Commercial and Medicare Supplemental claims databases. Patients with a VEEG between July 1, 2013 and December 31, 2016 were identified. Index eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In‐home EEG has demonstrated equitable diagnostic outcomes compared to gold standard inpatient monitoring 16 at a significantly lower cost, 10 making diagnostic assessments more accessible to a wider range of patient populations. However, in‐home assessments are only effective if used appropriately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In‐home EEG has demonstrated equitable diagnostic outcomes compared to gold standard inpatient monitoring 16 at a significantly lower cost, 10 making diagnostic assessments more accessible to a wider range of patient populations. However, in‐home assessments are only effective if used appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…8 Further, the natural environmental stressors of the patient's home may spur certain events that may not otherwise occur in an EMU setting. 7,9 Therefore, in-home vide EEG, when used effectively, offers a unique opportunity to reduce some of the burdens associated with costs and scheduling of inpatient assessments 10 and can support initiatives to improve access to diagnostic testing, specifically for the many epilepsy patients who live in rural regions or underserved communities. 11 With more flexibility in prescribing prolonged in-home EEG assessments, determining an optimal duration to observe typical, clinically relevant events is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who had undergone inpatient studies were found to be more likely to undergo subsequent additional inpatient testing, further contributing to an increase in long‐term costs. The same study also demonstrated that the time from physician referral to performance of the study was significantly shorter for HVET versus inpatient VT 13 . Due to an identical national tariff for inpatient VT and HVET in the UK National Health Service, the development of home recording was supported and found in the case of supervised recordings to be 30% cheaper than the inpatient recordings.…”
Section: Current Service Models For Hvetmentioning
confidence: 83%
“…Equipment is light and flexible and can be used indoors and out. No daily visits by a technician are needed, and the recording is unsupervised of the study was significantly shorter for HVET versus inpatient VT. 13 Due to an identical national tariff for inpatient VT and HVET in the UK National Health Service, the development of home recording was supported and found in the case of supervised recordings to be 30% cheaper than the inpatient recordings. In addition, at King's College Hospital, three inpatient VT beds were no longer required, and were converted to neurosurgical beds, allowing an extra 460 elective surgical cases to be treated.…”
Section: Yield Impact Costs and Economicsmentioning
confidence: 99%
“…Electrical safety can be established by avoiding electrical current leakage through proper use of fuses, outlets to ground the equipment, grounding electrode, and by avoiding use of extension cords. 56 Patients should be advised to avoid contact of the electrical machinery and wiring with water to maximize safety and minimize electrical current exposure that has been linked to skin burns and potentially more serious injury. 56 …”
Section: Safetymentioning
confidence: 99%